Reversible Hydrogenation–Oxidative Dehydrogenation of Quinolines over a Highly Active Pt Nanowire Catalyst under Mild Conditions. Issue 8 (6th May 2013) - Ge, Danhua; Hu, Lei; Wang, Jiaqing; Li, Xingming; Qi, Fenqiang; Lu, Jianmei; Cao, Xueqin; Gu, Hongwei
<x xml:space="preserve">Abstract</x> Over the wire and back again: The reversible hydrogenation–oxidative dehydrogenation of quinolines is reported by using Pt nanowire (NW) as the catalyst under mild reaction conditions. Pt NW shows high activity and selectivity in the hydrogenation of quinolines under H2 pressure (1 bar=100 kPa), and these hydrogenation products can be easily oxidized under the same conditions in an atmosphere of oxygen (1 bar) or in air.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>